Β2-МИКРОГЛОБУЛИН В ДИАГНОСТИКЕ НАСЛЕДСТВЕННЫХ СИНДРОМОВ С ПОРАЖЕНИЕМ ПОЧЕК У ДЕТЕЙ - Белькевич, Анна Геннадьевна; Козыро, Инна Александровна; Сукало, Александр Васильевич; Тур, Наталья Иосифовна (Медицина: теория и практика, 2020)